2020
DOI: 10.1155/2020/4910767
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Exacerbates TNF-α-Induced Proliferative Inhibition in Human Periodontal Ligament Stem Cells through Upregulation and Activation of TNF Receptor 1

Abstract: Objective. This research is aimed at investigating how high glucose affects the proliferation and apoptosis in periodontal ligament stem cells (PDLSCs) in the presence of TNF-α. Methods. PDLSCs obtained from periodontal healthy permanent teeth were treated under either high-glucose condition (30 mmol/L, G30 group) or normal glucose condition (5.6 mmol/L, G5.6 group) in the presence or absence of TNF-α (10 ng/ml) for 2 to 6 days. Cell proliferation and cell cycle were evaluated by CCK-8, EdU incorporation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The blockade of TNFR‐1 effectively recovered cell viability in the presence of both high‐glucose concentrations and TNF‐alpha, indicating that TNFR‐1 played a key role in mediating cell viability. In our previous study (Zhu et al, 2020), we found that the expression of TNFR‐2 was unchanged in the presence of high‐glucose concentrations. The blockade of TNFR‐2 through the use of an antibody did not restore cell viability against high‐glucose concentrations and TNF‐alpha.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The blockade of TNFR‐1 effectively recovered cell viability in the presence of both high‐glucose concentrations and TNF‐alpha, indicating that TNFR‐1 played a key role in mediating cell viability. In our previous study (Zhu et al, 2020), we found that the expression of TNFR‐2 was unchanged in the presence of high‐glucose concentrations. The blockade of TNFR‐2 through the use of an antibody did not restore cell viability against high‐glucose concentrations and TNF‐alpha.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous study demonstrated that CD146 + PDLCs isolated from human PDLCs presented higher colony efficiency and higher potential of osteogenic and adipogenic differentiation than those exhibited by CD146 − PDLCs. CD146 + PDLCs expressed MSC‐specific surface markers, including CD90, CD105, CD44, CD73, CD146, and Stro‐1 (Zhu et al, 2020, 2013). Additionally, CD146 − PDLCs exhibited little response to TNF‐alpha and expressed low levels of TNFR‐1 and TNFR‐2 (Zhu et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were divided into four groups: (1) Control group; (2) TNF-α group:stimulated with TNF-α (10 ng/ml) [17]alone for 24 hours; (3) -COOH + TNF-α group :preincubation with G4.5-COOH (7uM) for 4 h before TNF-α stimulation; (4) GW9662 +-COOH + TNF-α group : GW9662 (10uM/ml) [18]was added for 0.5 h and then preincubation with G4.5-COOH (7uM) for 4 h before TNF-α stimulation.…”
Section: Cells and Treatmentsmentioning
confidence: 99%